TÁCH VÀ BƯỚC ĐẦU NGHIÊN CỨU CÁC TOXIN NGẮN CỦA NỌC BÒ CẠP HETEROMETRUS LAOTICUS - Anh, Hoàng Ngọc; Minh Hoàng, Võ Đỗ; Ilya, Nikitin; Yuri, Utkin (Vietnam Journal of Chemistry, 2012)
The scorpion Heterometrus laoticus is wide distributed in the South-West Vietnam. The venom of this scorpion has an analgesic and anti-inflammatory activities. The crude venom of H. laoticus was separated into five fractions by column chromatography on Sephadex G-50. These fractions have different chemical and biological properties, one them (fraction 4) being toxic to mice, the other (fraction 5) - to crickets. Two of the fractions (fraction 2 and 5) affect the process of blood coagulation, while the crude venom has no such effect. Several polypeptides with molecular masses in the range from 2000 to 4000 Da were isolated from fraction 5 by combination of gel-filtration on Superdex HR75 column and RP-HPLC. By molecular masses these polypeptides can be assigned to the family of short scorpion toxins. Mass-spectrometry analysis showed that one H. laoticus toxin possesses the molecular mass of 3698.8 Da, which is similar to that of potassium channel toxin alpha-KTx 6.13 (3701 Da) isolated from Malaysian black scorpion H. spinifer. The structure and biological activity of the isolated toxins is under study.